Infection with different strains of SARS-CoV-2 in patients with COVID-19 - Hashim, Hayder O.; Mohammed, Mudher K.; Mousa, Mazin J.; Abdulameer, Hadeer H.; Alhassnawi, Alaa T.S.; Hassan, Safa A.; Al-Shuhaib, Mohamed Baqur S. (Archives of Biological Sciences, 2020)
Paper description: We examined the biological diversity of SARS-CoV-2 infection by investigating possible genetic variations of the spike glycoprotein in Iraqi patients with COVID-19. A 795 bp coding region within the viral spike (S) gene was amplified from 19 Nucleic acid variations showed co-infection with two different viral strains. Most samples had three nonsense single nucleotide polymorphisms (SNPs). Network and phylogenetic analyses indicated that all viral infections exhibited mixed evolutionary origins represented by multiple viral sources. Our findings indicate that defective SARS-CoV-2 relied on helper strains with intact spikes for infection. An alternative putative ACE2-independent viral infection route is also suggested. Abstract: The biological diversity of SARS-CoV-2 was assessed by investigating the genetic variations of the spike glycoprotein of patients with COVID-19 in Iraq. Sequencing identified fifteen novel nucleic acid variations with a variety of distributions within the investigated samples. The electropherograms of all identified variations showed obvious co-infections with two different viral strains per sample. Most samples exhibited three nonsense single nucleotide polymorphism (SNPs), p.301Cdel, p.380Ydel and p.436del, which yielded three truncated spike glycoproteins, respectively. Network and phylogenetic analyses indicated that all viral infections were derived from multiple viral origins. Results inferred from the specific clade-based tree showed that some viral strains were derived from European G-clade sequences. Our data demonstrated the absence of single-strain infection among all investigated samples in the studied area, which entails a higher risk of SARS-CoV-2 in this country. The identified high frequency of truncated spike proteins suggests that defective SARS-CoV-2 depend on helper strains possessing intact spikes during infection. Alternatively, another putative ACE2-independent route of viral infection is suggested. To the best of our knowledge, this is the first report to describe co-infection with multiple strains of SARS-CoV-2 in patients with COVID-19.